Feminisme Gelombang Kedua Dalam Film “Enola Holmes” - Teguh Dwi Putranto; Francesca Thalia Satiadhi; Arista Amelinda (PUBLIC CORNER, 2022)
Currently, media with the subject of women's rights are emerging, discussing women's issues and sexual orientation such as break-even relations, welfare, and sexual orientation disparities in various divisions. Films are no exception, where the issue of feminism is a genre that is widely discussed, one of which is in the film “Elona Holmes”. This study aims to find out how the second wave of feminism in the film “Elona Holmes” is. John Fiske's semiotics was chosen as a method in this research on the movie "Elona Holmes". The conclusion of this study is that the second wave of feminism in the film “Elona Holmes” represents women's empowerment which can make the audience feel optimistic and motivated to understand the gender equality movement. Keywords: Second Wave Feminism; Film; Semiotics; Women Empowerment; Gender Equality.